ORANGTUA DAN PENDIDIKAN ANAK DALAM PERSPEKTIF GRAVISSIMUM EDUCATIONIS DAN RELEVANSINYA BAGI SISTEM PENDIDIKAN DI INDONESIA - Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2018)
The first and primary educator for the child is the parents. As first and foremost educators, parents reveal the fundamental authority to educate their children. Educate children they should do, because they are parents. The task and the call of parents in educating their children is a task and a call that should not be replaced by anyone. No matter how great the other party in educating but will not be able to channel life to the child fully and intrinsically. They are unlikely to be able to fill the heart and soul of the child in building a complete relationship between the child and the parent and vice versa. The education that is the responsibility of the parent is an education that reflects a purpose. The purpose of education is essentially: the fostering of the human person as a whole, as both personal and social beings, within the framework of his final destiny. By looking at the purpose of education, it is not enough for parents to only form a child to be smart/clever, but also need to form a child's person to be a whole person. Laws that require parents to educate children, need to get support from the government well so that parents are able to carry out these obligations well too.